Reovirus-induced cell-mediated immunity for the treatment of multiple myeloma within the resistant bone marrow niche. Issue 3 (19th March 2021) - Müller, Louise M E; Migneco, Gemma; Scott, Gina B; Down, Jenny; King, Sancha; Askar, Basem; Jennings, Victoria; Oyajobi, Babatunde; Scott, Karen; West, Emma; Ralph, Christy; Samson, Adel; et al.
Abstract : Background: Multiple myeloma (MM) remains an incurable disease and oncolytic viruses offer a well-tolerated addition to the therapeutic arsenal. Oncolytic reovirus has progressed to phase I clinical trials and its direct lytic potential has been extensively studied. However, to date, the role for reovirus-induced immunotherapy against MM, and the impact of the bone marrow (BM) niche, have not been reported. Methods: This study used human peripheral blood mononuclear cells from healthy donors and in vitro co-culture of MM cells and BM stromal cells to recapitulate the resistant BM niche. Additionally, the 5TGM1-Kalw/RijHSD immunocompetent in vivo model was used to examine reovirus efficacy and characterize reovirus-induced immune responses in the BM and spleen following intravenous administration. Collectively, these in vitro and in vivo models were used to characterize the development of innate and adaptive antimyeloma immunity following reovirus treatment. Results: Using the 5TGM1-Kalw/RijHSD immunocompetent in vivo model we have demonstrated that reovirus reduces both MM tumor burden and myeloma-induced bone disease. Furthermore, detailed immune characterization revealed that reovirus: (i) increased natural killer (NK) cell and CD8 + T cell numbers; (ii) activated NK cells and CD8 + T cells and (iii) upregulated effector-memory CD8 + T cells. Moreover, increased effector-memory CD8 + T cells correlated with decreased tumor burden. Next, we explored the potential for reovirus-induced immunotherapy using human co-culture models to mimic the myeloma-supportive BM niche. MM cells co-cultured with BM stromal cells displayed resistance to reovirus-induced oncolysis and bystander cytokine-killing but remained susceptible to killing by reovirus-activated NK cells and MM-specific cytotoxic T lymphocytes. Conclusion: These data highlight the importance of reovirus-induced immunotherapy for targeting MM cells within the BM niche and suggest that combination with agents which boost antitumor immune responses should be a priority.